2009
DOI: 10.1130/g25550a.1
|View full text |Cite
|
Sign up to set email alerts
|

Variations in 238U/235U in uranium ore deposits: Isotopic signatures of the U reduction process?

Abstract: The ability to measure 238 U/ 235 U to high precision presents an important new opportunity to study the fate and transport of uranium in the environment. The ratio of 238 U/ 235 U was determined by multicollector-inductively coupled plasma-mass spectrometer in six uranium ore samples representing two different classes of deposits. Signifi cant offsets in 238 U/ 235 U are observed between uranium ores precipitated from groundwaters at low temperature versus hydrothermal deposits precipitated at high temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 22 publications
5
79
1
5
Order By: Relevance
“…The reproducibility of these standards was about 0.05‰ at Hannover and 0.1‰ at ASU (Table S7; all delta values there are reported relative to CRM-112A). The delta values for all standards used agree with those previously published (9,11,18,19,36) (Table S7).…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…The reproducibility of these standards was about 0.05‰ at Hannover and 0.1‰ at ASU (Table S7; all delta values there are reported relative to CRM-112A). The delta values for all standards used agree with those previously published (9,11,18,19,36) (Table S7).…”
Section: Methodssupporting
confidence: 86%
“…4). The results of this study suggest that, in many sedimentary deposits, enzymatic U reduction was a major driver for authigenic U enrichment, including marine sediments and shales (10,14), as well as sandstone tabular and roll-front U deposits (8,11,36). For example, in the modern Black Sea, U isotope fractionation (Δ 238 U) of ∼0.7‰ between the authigenic U in the sediment and that in the deep water column was observed (10,13,37).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…For these samples, the predominant fractionation mechanism has been generally assumed to be the NFS effect in the case of U(VI)/ U(IV) redox reactions. NFS effect leads to the enrichment of the heavy 238 U isotope into the U(IV) species (30)(31)(32). Some studies reported that these redox reactions can be mediated by sulfatereducing bacteria (33)(34)(35), but, in these cases, only extracellular uranium was analyzed, and the potential processes occurring inside the bacteria were not investigated.…”
Section: Significancementioning
confidence: 99%
“…More recently, the IUPAC (13) recommend a value of 137.80 from the analysis of six natural ore deposits (14), confirmed by high-precision isotope ratio analyses using the IRMM 3636 233 U-236 U double spike (15,16) whose isotopic composition is traceable to SI units. The invariance of the present-day 238 U/ 235 U ratio has been brought into question by studies that have demonstrated U isotopic fractionation in terrestrial materials (17)(18)(19)(20). Such fractionation occurs during oxidation-reduction reactions (U VI to/from U IV ), coordination change during adsorption, or leaching, and is due to thermodynamic or nuclear field shift effects (21)(22)(23).…”
mentioning
confidence: 99%